A Closed-Loop Supply Chain Problem with Retailing and Recycling Competition. (24th July 2014) - Xu, Chuanchao; Li, Bo; Lan, Yanfei; Tang, Yi
Abstract : We investigate a durable product retailing and recycling problem in a closed-loop supply chain consisting of a single manufacturer and two competitive retailers, in which the manufacturer collects used products via retailers from the consumers and has sufficient channel power over the retailers to act as a Stackelberg leader; the retailers compete in retail products and recycling used products. In order to analyze the impact of retailing and recycling competitions on the profits of the manufacturer and the competitive retailers, two collection models (coordinated collection (Model C ) and decentralized collection (Model D )) are established, respectively. Then, based on game theory, we derive the optimal retail price, the optimal repurchase price, and the optimal profits of the manufacturer and the retailers. The managerial insights demonstrate that more intense retailing competition induces the increase of the manufacturer's profits in both forward and reverse channels and retailers' profits in the forward channel and the decrease of retailers' profits in the reverse channel, while more intense recycling competition induces the decrease of the profits of the manufacturer and retailers in both forward and reverse channels. Finally, numerical examples are given to illustrate the effectiveness of the proposed models.